The Influence of School Principal Managerial Skills on Teacher Performance at Mts Nurul Hidayah Leuwisadeng Bogor - Agus Tamami; Sifa Ulqolbi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Educational institutions require a high level of coordination, so the success of education is also the success of the principal himself. So there is a need for management to realize the success of education in schools. Management itself is the art of organizing and managing existing resources within the institution to achieve effective and efficient goals. The purpose of this study was to determine whether there was an effect of principal's managerial skills on teachers at MTs Nurul Hidayah Leuwisadeng Bogor. In this study, descriptive quantitative research methods were used, and based on the results of the research and data analysis that the researchers did, the results showed that the t count was 3.291 when compared to the t table of 0.468, so it was said that t count > t table which means the principal managerial skills variable (x) on the teacher performance variable (y) has a significant effect. And with the value of the coefficient of determination R square of 0.404, which means that if the teacher's performance has an influence, it can improve teacher performance, with a value of 40.4%. The remaining aspects of teacher performance are influenced by other factors not examined in this study.